Natural disasters, deforestation, and emissions affect economic growth in Somalia - Abdimalik Ali Warsame; Jama Mohamed; Samuel Asumadu Sarkodie (Heliyon, 2024)
This study ascertains the effect of natural disasters, deforestation, and emissions on economic growth in Somalia using annual time series spanning 1990–2018. Contrary to previous attempts, this study utilized the kernel regularized least squares (KRLS) technique, robust Granger causality in the presence of instabilities, and novel supremum right-tail Augment Dickey-Fuller unit root to test explosive behaviors in data series. While two date-stamped explosive behaviors are detected in economic growth (2003–2012, 2014–2016) and FDI (2004, 2016–2018), one explosive behavior is observed in capital formation (2010–2018) and population density (2010–2018). Moreover, time-varying granger causalities among sampled variables are observed. The empirical results show natural disasters and deforestation significantly undermine economic growth, whereas GHG emissions stimulate economic growth. Besides, while GHG emissions have increasing marginal effects, natural disasters and deforestation have decreasing marginal effects. The marginal effect of the interaction between natural disasters and temperature change is close to zero, implying that temperature changes do not mediate the disaster-growth nexus. Nevertheless, the study underscores the need for the implementation of environmental and economic policy reforms related to natural disaster preparedness, eliminating deforestation for charcoal exports while implementing a paradigm shift from domestic charcoal and firewood energy consumption to clean and renewable energy.